Transcultural negotiations of gender : studies in (be)longing - Bhaduri, Saugata; Mukherjee, Indrani (Springer, 2016)
Transcultural Negotiations of Gender probes into how gender is negotiated along the two axes of `belonging' and `longing'- the twin desires of being located within a cultural milieu, while yearning for either what has passed by or what is yet to come.